Contingency, Absurdity and Human Conflict in Sartre’s Philosophy - Dagnachew Assefa (Ethiopian Journal of the Social Sciences and Humanities, 2020)
This article is centered on two of Sartre’s literary works: “Nausea” and “No Exit” along with his dialectical theory of the ‘Look’ in Being and Nothingness. I believe that these three texts represent not three distinct perspectives but rather different sets of approach to the same problem i.e. the phenomenon of human relationship. It is with this point in mind that I develop the following interrelated claims. First, even though Sartre intended to bring a new language and mode of articulation in his later works, the fundamental features of his philosophy remained the same. Thus, issues that are foundational to his early writing including the self/other relationship, the for-itself as project, the contingent reality of the world, the resistance of the in-itself/ materiality all figure high in his later writings as well. Second, as opposed to any social philosophy which accepts the possibility of a harmonious relation between human beings Sartre perceived the essence of human relations not as mitesein (‘being-with’), but rather as conflict. I submit that the source of Sartre’s problem lies in his very model of social relations given that his social ontology does not allow him to incorporate what Maurice Marleau-Ponty calls the "inter-world". This paper is also informed with the belief that although Sartre the intellectual and the creative artist are closely joined together, essentially, the novelist is much more assuring than the philosopher. Thus, even when he is not writing a literary composition proper he displays a unique talent of putting his philosophical ideas in artistic and dramatic terms. I use Sartre’s phenomenological description of the dialectic of the "look" (Le Regard) to demonstrate this point. The final section of the paper is devoted to a critical examination of Sartre’s philosophical positions developed in the works discussed above.